Inhibition of Senescence‐Associated Genes Rb1 and Meis2 in Adult Cardiomyocytes Results in Cell Cycle Reentry and Cardiac Repair Post–Myocardial Infarction. Issue 15 (6th August 2019) - Alam, Perwez; Haile, Bereket; Arif, Mohammed; Pandey, Raghav; Rokvic, Miso; Nieman, Michelle; Maliken, Bryan D.; Paul, Arghya; Wang, Yi‐Gang; Sadayappan, Sakthivel; Ahmed, Rafeeq P. H.; Kanisicak, Onur
Abstract : Background: Myocardial infarction results in a large‐scale cardiomyocyte loss and heart failure due to subsequent pathological remodeling. Whereas zebrafish and neonatal mice have evident cardiomyocyte expansion following injury, adult mammalian cardiomyocytes are principally nonproliferative. Despite historical presumptions of stem cell–mediated cardiac regeneration, numerous recent studies using advanced lineage‐tracing methods demonstrated that the only source of cardiomyocyte renewal originates from the extant myocardium; thus, the augmented proliferation of preexisting adult cardiomyocytes remains a leading therapeutic approach toward cardiac regeneration. In the present study we investigate the significance of suppressing cell cycle inhibitors Rb1 and Meis2 to promote adult cardiomyocyte reentry to the cell cycle. Methods and Results: In vitro experiments with small interfering RNA–mediated simultaneous knockdown of Rb1 and Meis2 in both adult rat cardiomyocytes, isolated from 12‐week‐old Fischer rats, and human induced pluripotent stem cell–derived cardiomyocytes showed a significant increase in cell number, a decrease in cell size, and an increase in mononucleated cardiomyocytes. In vivo, a hydrogel‐based delivery method for small interfering RNA–mediated silencing of Rb1 and Meis2 is utilized following myocardial infarction. Immunofluorescent imaging analysis revealed a significant increase in proliferation markers 5‐ethynyl‐2′‐deoxyuridine, PH3, KI67, and Aurora B in adult cardiomyocytes as well as improved cell survivability with the additional benefit of enhanced peri‐infarct angiogenesis. Together, this intervention resulted in a reduced infarct size and improved cardiac function post–myocardial infarction. Conclusions: Silencing of senescence‐inducing pathways in adult cardiomyocytes via inhibition of Rb1 and Meis2 results in marked cardiomyocyte proliferation and increased protection of cardiac function in the setting of ischemic injury.